Role Of Attitude, Norma, Availability And Success Satisfaction In Furniture Companies In Sukoharjo District - Aris Tri Haryanto; Anggoro Panji Nugroho (Journal of Indonesian Science Economic Research, 2019)
The purpose of this study was to determine and test the role of attitude, norms, willingness to continue and satisfaction of succession in furniture companies in Sukoharjo regency. The analysis technique in this study used the instrument test, t test, F test, coefficient of determination test and path analysis. Attitude positive and significant effect on the willingness to continue. Norms have a negative and not significant effect on willingness to continue. Attitude positive and significant effect on succession satisfaction. Norms have a positive and significant effect on succession satisfaction. Willingness to continue a positive and significant effect on succession satisfaction. Conclusions Direct and Indirect Effects are as follows: The direct effect of attitudes on succession satisfaction results in greater value than indirect effects, so it is more effective through direct pathways. The direct effect of norms on succession satisfaction results in greater value than indirect effects, so it is more effective through the direct path.